Strengthening the Ethics of the Deontology of Local Media Journalists in the Disruption Era - Mubarok Mubarok; Billy K. Sarwono; Fitria Angeliqa (Jurnal the Messenger, 2024)
Introduction: This study aims to describe the important role of organizational culture in strengthening the deontology ethics of local media journalists. Deontological ethics states that the will to do good must arise from within a person's individual. Organizational culture is one of the means used to instill, strengthen and internalize these values. Technological disruptions that have an impact on changes in media consumption, the closure of print media, the development of online media have changed the dynamics of journalistic practice in Indonesia. The important role of ethics comes to the fore in maintaining the quality of local media journalistic practices.